The Significance of RUNX3 Expression Levels in the Prognosis of Severe Acute Pancreatitis - Cheng YH; Cao LF (International Journal of General Medicine)
Ya-Hui Cheng, Lun-Fei Cao Emergency Department, Zhoukou Central Hospital, Zhoukou, People’s Republic of ChinaCorrespondence: Ya-Hui Cheng, Email cbi011@yeah.netObjective: To analyze the expression levels of RUNX3 in patients with severe acute pancreatitis (SAP) and its impact on disease progression.Methods: Healthy individuals undergoing physical examinations during the same period were selected as a control group. General patient data were analyzed and compared. Enzyme-linked immunosorbent assay (ELISA) was used to detect the expression levels of RUNX3, and differences in RUNX3 levels between the groups were compared.Results: Comparison of general characteristics showed no statistically significant differences in sex, age, body mass index (BMI), history of diabetes, hypertension, coronary artery disease, etiology, or prevalence of fatty liver among the groups (P > 0.05). The time from onset to admission and the length of hospital stay were significantly higher in the severe group compared to the mild group (P = 0.001). The severe group also exhibited significantly higher white blood cell counts (WBC), procalcitonin (PCT), C-reactive protein (CRP), lipase (LPS), and APACHE II scores (P = 0.001). RUNX3 levels were 97.67 ± 31.03 in the SAP group, significantly lower than 137.22 ± 53.07 in the mild group and 217.55 ± 76.59 in the control group (P < 0.05). Pearson correlation analysis revealed a negative correlation between RUNX3 levels and APACHE II scores in patients with acute pancreatitis (r = − 0.613, P < 0.0152). RUNX3 levels in the poor prognosis group were significantly lower than those in the good prognosis group (P < 0.05). ROC curve analysis indicated that the area under the curve for RUNX3 levels in predicting the prognosis of acute pancreatitis was 0.835, with an optimal cutoff value of 162.31 pg/mL, a sensitivity of 90.00%.Conclusion: RUNX3 expression levels are significantly reduced in patients with SAP and are negatively correlated with disease severity, making them a potential biomarker for assessing and predicting the prognosis of acute pancreatitis.Keywords: severe acute pancreatitis, RUNX3, disease progression